Athematical model of the complex dynamic system "perturbation influences-machine- operator" - P. A. Korchagin; I. A. Teterina (Вестник СибАДИ, 2017)
The authors describe a mathematical model of the dynamic system "perturbation influences-machine- operator". There is presented a design scheme of a road sweeping machine (RSM) on the basis of MTZ-80. There is carried out a method of forming dynamic equation for complex dynamic systems "perturbation influences-machine- operator". Also the article reflects calculation dependences for determining perturbation dependences from the direction of micropattern, power installation and brush-type operating device.